'My attention shifted from the material I was teaching to student learning': the impact of a community of practice on teacher development for new international academics. Issue 5 (20th October 2021) - Kensington-Miller, Barbara
ABSTRACT: Supporting new academics when they begin a university career is important for them to adapt quickly and easily to the institutional goals and expectations. For those arriving from overseas and a different culture, often with families, this support is even more crucial. In this article, 10 academics from a range of disciplines, in which nine were both new to the university and New Zealand, were involved in a development programme over one semester while they worked in their respective departments. As the group met regularly, a community of practice developed, providing the right mix of necessary information for newcomers and community support as they learned about the institutional expectations of academic life. With an emphasis on teaching to move from being predominantly teaching-focused to learning-focused and with the group support, the participants experimented with making changes to their teaching practices. The findings illustrate four different phases of development occurred and highlights the need for well-designed induction programmes that are not the traditional, one-size-fits-all. Importantly, with international numbers continuing to increase, creating communities of practice within induction programmes and building teacher identity will enable newcomers to the academy to grow in confidence of who they are professionally.